34.3k views
14 votes
What is the sequence of the n^"th" term equation f(n) = -3n +7 for n 1

User Chris Lear
by
5.9k points

1 Answer

13 votes

Answer:

The sequence of the given equation

4 , 1, -2 , -5, ......

∴ The given sequence is in Arithmetic progression ( A.P)

Explanation:

Step(i):-

Given
n^(th) term of thesequence

f (n) = - 3n + 7

Put n = 1

first term a₁ = f (1 ) = - 3 (1 ) + 7 = - 3 + 7 = 4

Put n = 2

second term a₂ = f(2) = - 3 ( 2) + 7 = -6 +7 =1

Put n =3

Third term a₃ = f(3) = -3(3) +7 = -9 + 7 = -2

Put n =4

Fourth term a₄ = f(4) = -3(4) +7 = -12 + 7 = -5

Step(ii):-

The sequence of the given equation

4 , 1, -2 , -5, ......

first term a = 4 , d = 1 -4 = -3

The difference of two terms in this sequence is equal

∴ The given sequence is in Arithmetic progression ( A.P)

Final answer:-

The sequence of the given equation

4 , 1, -2 , -5, ......

∴ The given sequence is in Arithmetic progression ( A.P)

User Zimmer
by
6.2k points